2011
DOI: 10.1007/s00404-011-2018-3
|View full text |Cite
|
Sign up to set email alerts
|

Submental lymph node metastasis from invasive ductal breast carcinoma

Abstract: This case report presents a 52-year-old woman with a submental swelling which arose 3 years after wide local excision and axillary lymphadenectomy for breast carcinoma. Histopathological examination after excision biopsy of this lesion confirmed the presence of invasive breast carcinoma in a submental lymph node. Computed tomography of the head, neck, thorax, abdomen and pelvis demonstrated multiple brain and pulmonary metastases. Further management was palliative and the patient died 5 months later. This is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The incidence of NM of 3% in the present study is comparable to that previously reported at 4% (13). BC can metastasize to different head and neck regions, although the most common site is the supraclavicular fossa (14)(15)(16). A recent study (17) explored patterns of metastasis to the head and neck region and demonstrated extreme variability in the clinical and pathological features of BC metastasis.…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of NM of 3% in the present study is comparable to that previously reported at 4% (13). BC can metastasize to different head and neck regions, although the most common site is the supraclavicular fossa (14)(15)(16). A recent study (17) explored patterns of metastasis to the head and neck region and demonstrated extreme variability in the clinical and pathological features of BC metastasis.…”
Section: Discussionsupporting
confidence: 87%
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“…The new therapies developed, during last decades, to be less harmful for the patients, as surgery and chemotherapy, were found to have, in too many cases, a relatively low successful rate and a high risk of reoccurrence [ 2 ]. The main problem with therapeutic molecules, including those from natural sources, concerns their insufficient selectivity and consequently their deleterious effects towards healthy cells [ 3 , 4 ]. Moreover, cancerous cells develop frequently mechanisms of resistance and particularly through the pumping of anticancer drugs outside their cytosol [ 5 ].…”
Section: Introductionmentioning
confidence: 99%